Responsabilidad internacional - Rey Caro, Ernesto J.; Drnas de Clément, Zlata; Mathieu, Esther; Pagliari, Arturo Santiago; Rodríguez, María Cristina; Salas, Graciela R.; Sartori, Marta Susana; Sticca, María Alejandra (2024)
Fil: Rey Caro, Ernesto J. Academia Nacional de Derecho y Ciencias Sociales de Córdoba; Argentina.